Changing attitudes towards management of men with locally advanced prostate cancer following radical prostatectomy: A follow‐up survey of Australia‐based urologists. Issue 6 (27th June 2016) - Brown, Bernadette; Egger, Sam; Young, Jane; Kneebone, Andrew B; Brooks, Andrew J; Dominello, Amanda; Haines, Mary
Abstract: Introduction: This study examined whether there has been change among Australia‐based urologists' knowledge, attitudes and beliefs relating to guideline‐recommended adjuvant radiotherapy for men with adverse pathologic features following radical prostatectomy since a prior survey in 2012 and investigated associations between attitudes and treatment preferences. Methods: A nationwide survey of Australia‐based urologist members of the Urological Society of Australia and New Zealand. Results: Ninety‐six respondents completed the 2015 survey (30% response rate) compared with 157 (45% response rate) in 2012. There was no significant change in awareness of national clinical practice guidelines for the management of prostate cancer. When considering adjuvant against salvage radiotherapy, urologists were significantly less favourable towards adjuvant radiotherapy in 2015 than in 2012 for two of three hypothetical clinical case scenarios with a high 10‐year risk of biochemical relapse according to Memorial Sloan Kettering Cancer Center nomograms ( P  < 0.001 for both cases). In 2015, urologists were less positive overall towards the recommendation for post‐operative adjuvant radiotherapy for men with locally advanced prostate cancer than in 2012 ( P  < 0.001), reflecting a significant change across a number of attitudes and beliefs. Of note, urologists felt other urologists would more likely be critical if they routinely referred the target patient group for radiotherapy in 2015 compared with 2012 ( P  = 0.007). Conclusion: In 2015 Australia‐based urologists were less favourable towards adjuvant radiotherapy over watchful waiting for men with high‐risk pathologic features post‐prostatectomy than in 2012. We could find no new published research that precipitated this change in attitude.